2017
DOI: 10.1037/neu0000342
|View full text |Cite
|
Sign up to set email alerts
|

Contralateral interictal and ictal EEG epileptiform activity accentuate memory impairment in unilateral mesial temporal sclerosis patients.

Abstract: Our results suggest that contralateral electrographic involvement in uMTS was associated with more pronounced memory impairment for verbal material in left discordant patients, and to a lesser extent, for nonverbal material in right discordant patients. Left discordant group also had increased memory complaints. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
(56 reference statements)
0
6
0
Order By: Relevance
“…Many patients with unilateral mTLE also showed significant contralateral interictal and ictal epileptiform activity during scalp and invasive electroencephalogram (EEG) recordings, which was thought to be related to surgical outcome and memory impairment ( Passarelli et al, 2015 , Jehi et al, 2010 , Pinto et al, 2017 ). Does abnormal ipsilateral hippocampus affect the contralateral hippocampus which seemed normal?…”
Section: Introductionmentioning
confidence: 99%
“…Many patients with unilateral mTLE also showed significant contralateral interictal and ictal epileptiform activity during scalp and invasive electroencephalogram (EEG) recordings, which was thought to be related to surgical outcome and memory impairment ( Passarelli et al, 2015 , Jehi et al, 2010 , Pinto et al, 2017 ). Does abnormal ipsilateral hippocampus affect the contralateral hippocampus which seemed normal?…”
Section: Introductionmentioning
confidence: 99%
“…The same EEG classification strategy was adopted in previous studies that demonstrated that bilateral epileptiform activity negatively impacts verbal and nonverbal memory in unilateral HS patients 14,15 . Based on these studies, we hypothesized that patients with bilateral electrographic ictal involvement would present less pronounced postoperative memory decline when compared to patients with ictal involvement restricted to the HS side.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with unilateral HS and bilateral epileptiform activity present worse baseline cognitive performance compared to patients with epileptiform activity restricted to the HS side. 14,15 Epileptiform activity contralateral to the HS side may be reverted after successful epilepsy surgery, leading to improved function in the contralateral hippocampus.…”
Section: Introductionmentioning
confidence: 99%
“…Second, epileptiform EEG activity may have negatively affected performance in our patient sample with chronic therapy‐refractory epilepsy. A recent study showed an impairment in the visual Stroop paradigm only in patients with unilateral HS who had concordant epileptiform EEG activity while patients with contralateral EEG epileptiform activity showed preserved Stroop test performance (Pinto et al , ). However, a previous review across various studies concluded that direct effects of epileptiform EEG discharges on cognition are rather mild (Aldenkamp & Arends, ).…”
Section: Discussionmentioning
confidence: 99%
“…Few neuropsychological studies used paradigms specifically targeting conflict resolution. An impairment in the colour word Stroop task was indicated in two studies (Pinto et al , ; Wang et al , ), whereas another study found no differences between mesial TLE and frontal epilepsy (Corcoran & Upton, ). In contrast to the fMRI findings in healthy subjects showing left lateralized BOLD responses during conflict resolution (Bach et al , ; Oehrn et al , ), the neuropsychological studies did not report a lateralization effect for unilateral mesial TLE.…”
Section: Introductionmentioning
confidence: 98%